Етапи розвитку туризму як соціально-економічного й культурно-освітнього явища - Шевчук, Андрій; Shevchuk, Andrey (Східноєвропейський національній уніерситет ім.Лесі Українки, 2013)
Аналіз літературних джерел дав підставу визначити основні етапи розвитку туризму (пізнавально-тор- говельний, освітньо-виховний, організаційний, радянський, сучасний). Пізнавально-торговельний період харак- теризується відкриттям нових земель, вивченням культури народів, військовими походами та спортивними змаганнями; освітньо-виховний – появою організованих форм туризму, спрямованістю на різнобічне виховання дітей; організаційний – створенням туристичних товариств, клубів, розробкою окремих методик туристич- ної підготовки; радянський – створенням туристичних структур, матеріальної бази; розвитком самодіяль- ного туризму; сучасний – програмно-нормативним забезпеченням, розвитком міжнародного туризму. The analysis of literature has allowed to determine main stages of the tourism development (cognitivecommercial, educative, organizational, Soviet, and modern). The cognitive-trading stage is characterized by the discovery of new lands, the study of people’s culture, military campaigns , and sports competitions. The educative stage is characterized by the emergence of the organized forms of tourism and by the focus on multidimensional parenting. The organizational stage is characterized by the creation of travel companies, clubs, and by the development of individual techniques of tourism training. The Soviet stage is characterized by the creation of travel agencies, the development of amateur tourism, and the creation of the material base. The modern stage is characterized by the creation of the program and regulatory support, and the development of international tourism.
Stages of the Development of Tourism as a Socio-economic, Cultural, and Educational Phenomenon
Keywords: туризм; історія розвитку; етапи розвитку; tourism; the history of the development; the stages of the development